Weed control and selectivity herbicides pre emerging in garlic cultivars - Guerra,Naiara (2020)
Abstract Background: Garlic cultivation is characterized by low capacity of competition with weed, mainly due to the characteristics of the canopy and it´s slow initial growth that make it difficult to cover the soil. Objective: This work aimed to evaluate the efficiency and selectivity of herbicides applied in the pre-emergence of two garlic cultivars in the edaphoclimatic condition of Santa Catarina State. Methods: Two experiments were carried out in the commercial garlic area with Ito and Chonan cultivars. Both experiments were conducted in randomized block design. The traits for Ito cultivar were without weed control, with weed control, with linuron (810 g ha-1), diuron (1,000 g ha-1), pendimethalin (1600 g ha-1), S-metolachlor (1200 g ha-1), oxyfluorfen (720 g ha-1) or flumioxazin (40 g ha-1). For the experiment with Chonan cultivar the treatment composed by oxadiazon (1000 g ha-1) was included. The analyzed variables were based on weed community control and phytotoxicity, stand, diameter of bulbs and productivity of garlic. Results: The infesting species of the experiment with the cultivar Ito were Stellaria media and Stachys arvensis, whereas for Chonan, only the first was found. The herbicides applied in pre-emergence were efficient in controlling these species until 45 days after application - DAA. The highest injuries at 45 DAA were caused by S-metolachlor, with 33% for Ito cultivar and 10% for Chonan. The best herbicides, taking into account weed control and productivity, were pendimethalin and S-metolachlor, for the Ito cultivar, and pendimethalin, oxyfluorfen, and flumioxazin for the Chonan cultivar. Conclusions: The pendimethalin stood out for presenting excellent weed control and being selective for both garlic cultivars.